2011
DOI: 10.1089/ten.tea.2011.0152
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-Beta 3 Stimulates Cartilage Matrix Elaboration by Human Marrow-Derived Stromal Cells Encapsulated in Photocrosslinked Carboxymethylcellulose Hydrogels: Potential for Nucleus Pulposus Replacement

Abstract: Degeneration of the nucleus pulposus (NP) has been implicated as a major cause of low back pain. Tissue engineering strategies using marrow-derived stromal cells (MSCs) have been used to develop cartilaginous tissue constructs, which may serve as viable NP replacements. Supplementation with growth factors, such as transforming growth factor-beta 3 (TGF-β3), has been shown to enhance the differentiation of MSCs and promote functional tissue development of such constructs. A potential candidate material that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 57 publications
2
59
0
Order By: Relevance
“…Oxidized dextran and N-carboxyethyl chitosan were synthesized in the laboratory as described previously. 16 Aqueous solutions of 20% teleostean, 3% N-carboxyethyl chitosan, and 7.5% oxidized dextran were mixed at ratio of 1:1:2. The hydrogel was cast between two glass plates and constructs of 4-mm diameter · 2.25-mm thick were produced using a biopsy punch.…”
Section: Mechanical Evaluation Of Crosslinking Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized dextran and N-carboxyethyl chitosan were synthesized in the laboratory as described previously. 16 Aqueous solutions of 20% teleostean, 3% N-carboxyethyl chitosan, and 7.5% oxidized dextran were mixed at ratio of 1:1:2. The hydrogel was cast between two glass plates and constructs of 4-mm diameter · 2.25-mm thick were produced using a biopsy punch.…”
Section: Mechanical Evaluation Of Crosslinking Kineticsmentioning
confidence: 99%
“…Many promising biomaterials are being investigated, including hyaluronic acid composite hydrogels, [10][11][12][13][14][15] photo-crosslinked carboxymethylcellulose hydrogels, 16,17 and many others. It has been suggested that the ideal hydrogel for NP augmentation and repair would (1) be suitable for minimally invasive (percutaneous) delivery to the NP space, (2) solidify rapidly after implantation to avoid leakage of cells or gel, (3) be capable of restoring disc structure and function, (4) be biologically compatible with the existing NP cell population, and (5) support cell growth and matrix deposition by codelivered cells, including native and stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) cultures have been used to induce BMSCs to differentiate into chondrocyte-like cells. These include cell pellet, alginate bead, hydrogel, and engineered 3D scaffold [20][21][22][23][24]. Chondrocyte-like phenotype can also be obtained via a single monolayer coculture of BMSCs, either with NPC or annulus fibrosis (AF) cells with cell-cell contact [25,26].…”
Section: The Finding Of Disc Progenitor Cellsmentioning
confidence: 99%
“…Human MSCs were purified from bone marrow (AllCells, Emeryville, CA, USA) using enriched density centrifugation as previously described (Gupta et al 2011;Chen et al 2013). Briefly, a Human MSC Enrichment Cocktail (StemCell Technologies, Vancouver, BC, Canada) (Lee et al 2005) was added to the bone marrow and incubated for 20 min to allow for unwanted cells and red blood cells to be crosslinked via tetrameric antibody complexes.…”
Section: Primary Cell Isolationmentioning
confidence: 99%
“…Carboxymethylcellulose (CMC), a watersoluble polysaccharide derivative of cellulose (Klemm et al 2005), has also been evaluated as an NP tissue scaffold due to its biocompatibility, low-cost, FDAapproval and commercial availability in high purity forms (Ogushi et al 2007). Recently, photocrosslinked CMC hydrogels were shown to support cell viability and the assembly of functional extracellular matrix (ECM) by encapsulated human marrow-derived mesenchymal stromal cells (hMSCs) when cultured in serumfree, chemically defined medium supplemented with TGF-β3 (Gupta et al 2011). However, the mechanical functionality of these constructs did not achieve native levels of the NP (Cloyd et al 2007), providing motivation to refine hydrogel fabrication parameters in order to improve mechanical properties.…”
Section: Introductionmentioning
confidence: 99%